School Head Stewardship in Enhancing Secondary School Students’ Academic Results - Onikoyi, Olawale Abayomi; Akinnubi, Olaolu Paul; Yusuf, Jamila; Olaifa, Adeseko Sunday; Ayoku, Oba Babatunde (Gagasan Pendidikan Indonesia, 2024)
This study aimed to determine, clarify, and evaluate school heads' academic principles as a first step toward enhancing secondary school students’ academic results. The research methodology employed was a systematic literature review. The most crucial component of enhancing student academic results is school head stewardship; school heads must engage in good academic in their stewardship before they can enhance the quality of education. Drawing from Weber and Murphy's instructional stewardship model, it can be deduced that good instructional stewardship entails the following: creating a school's vision, mission, and goals; creating learning programs that can fulfill needs; fostering an environment of academic in the workplace and establishing an academic learning climate. Encourage and carry out thorough academic evaluations. A multifaceted concept, principle instructional stewardship focuses on how school heads plan and carry out coordination duties in the secondary school environment. Building a synergistic relationship with every secondary school students in the school is essential to creating a successful learning habits, so that technology can become a useful tool rather than an obstacle in the learning process.